Towards High Speed of All-Optical Logic and Switches Using Semiconductor Optical Amplifiers - Zhou, Peng; Yang, Xuelin; Wang, Gang; Hu, Weisheng (Recent Patents on Electrical & Electronic Engineering, 2013)
All-optical logic gate and switch are the key elements for ultrafast (>100 Gbit/s) signal processing in highspeed optical networks. Recent progress and related patents on all-optical logic gates based on semiconductor optical amplifiers (SOAs) are reviewed and optical switches with various configurations are discussed. The frequency-domain analysis of the turbo-switch (TS) incorporating two cascading SOAs is presented in detail to explore its ultimate operation bandwidth. The results show that the 3dB bandwidth of the TS is 300 GHz, which can be a good candidate for ultrafast all-optical switches.
Keywords: semiconductor optical amplifier